Pulmonary Tumor Embolism and Pulmonary Tumor Thrombotic Microangiopathy Causing Rapidly Progressive Respiratory Failure: A Case Series - Rajdev, Kartikeya; Madan, Ujjwal; McMillan, Sean; Wilson, Kyle; Fisher, Kurt; Hein, Ashley; Patil, Amol; Bista, Sabin; Hershberger, Daniel; Boer, Brian (JIM - high impact case reports, 2022)
Pulmonary tumor embolism (PTE) and pulmonary tumor thrombotic microangiopathy (PTTM) are rare etiologies for rapidly progressive dyspnea in the setting of undiagnosed metastatic cancer. They occur most frequently in association with adenocarcinomas, with PTE being most frequently associated with hepatocellular carcinoma and PTTM being most commonly reported with gastric adenocarcinoma. Pulmonary tumor embolism and PTTM appear to be a disease spectrum where PTTM represents an advanced form of PTE. Pulmonary tumor embolism and PTTM are mostly identified postmortem during autopsy as the antemortem diagnosis remains a clinical challenge due to the rapidly progressive nature of these rare diseases. We report 2 cases of rapidly progressive respiratory failure leading to death, due to tumoral pulmonary hypertension resulting from PTE and PTTM, diagnosed postmortem. Both of the patients were middle-aged females, nonsmokers, and had a gastrointestinal source of their primary malignancy.